Genetic algorithm optimisation for fuzzy control of wheelchair lifting and balancing - Ahmad, Salmiah; Tokhi, M. Osman; Toha, Siti Fauziah (2009)
In this paper, an optimisation technique is adopted to manipulate the input and output scaling of a fuzzy logic controller for lifting the front wheels of a wheelchair and stabilizing the wheelchair in two-wheeled mode. A virtual wheelchair (WC) model is developed within Visual Nastran (VN) software environment where the model is further linked with Matlab/Simulink for control purposes. The lifting of the chair is done by transforming the first link, attached to the front wheels (casters) to the upright position while maintaining stability of the second link where the payload is attached. General rules of thumb allow heuristic tuning of the parameters but a proper optimisation mechanism will perform better. Genetic Algorithm is used to control the two-wheeled wheelchair and results show that the optimised parameters give better system performance.